Orange Peel Essential Oil Nanoemulsions Supported by Nanosilver for Antibacterial Application - Doan Van Dat; Nguyen Van Cuong; Pham Hoang Ai Le; Tran Thi Lan Anh; Pham Tan Viet; Nguyen Thi Lan Huong (Indonesian Journal of Chemistry, 2020)
This study is devoted to the synthesis of King Orange peel essential oil in water nanoemulsions combined with nanosilver by ultrasonic method supported by mechanical stirring for antibacterial application. The samples were characterized by Gas chromatography-mass spectrometry (GC-MS), Ultraviolet–visible (UV-Vis), Transmission electron microscopy (TEM), and Dynamic light scattering (DLS) methods. According to the above-experimental results, it was found that the emulsions based on orange essential oil (without nanosilver) and the ones combined with nanosilver have the average particle size from 66.2 nm and 42.9 nm, respectively. The obtained nanoemulsions were also tested to examine their antibacterial ability against Escherichia coli (E. coli) by the disc diffusion method. It has been also found that nanoemulsions based on orange essential oil supported by nanosilver have the superior antibacterial ability, compared with individual components of the materials.